One-step CO assisted synthesis of hierarchical porous PdRuCu nanosheets as advanced bifunctional catalysts for hydrogen evolution and glycerol oxidation. (12th September 2022) - Wang, Jing; Zhang, Wen; Dong, Zemeng; Zhang, Ning; Zhang, Qiong; Xie, Congxia; Wu, Zexing; Xu, Guang-Rui; Wang, Lei
Abstract: Pd-based catalysts have received wide attention due to their outstanding anti-CO poisoning property, whereas the structural instability limits their application. The hierarchical porous PdRuCu nanosheets (HP PdRuCu NSs) with large electrochemically active surface area, abundant active sites, and stable structures are synthesized through continuous access to CO bubbles. HP PdRuCu NSs exhibit excellent hydrogen evolution reaction (HER) catalytic activity with an ultralow overpotential of 25 mV at 10 mA cm −2 and a Tafel slope of 87.5 mV dec −1 in alkaline·media. Meanwhile, the peak mass activity and specific activity of HP PdRuCu NSs for glycerol oxidation reaction (GOR) are 1083 mA mg −1 Pd and 38.8 A m −2, respectively, superior to that of PdRu nanosheets (PdRu NSs), Pd nanosheets (Pd NSs), and commercial Pd black. The introduction of Ru and Cu atoms facilitates the C–C bond cleavage and the complete oxidation of glycerol to CO2, as well as the accelerated oxidation/removal of the poisonous COads in between. Graphical abstract: Image 1 Highlights: The obtained HP PdRuCu NSs with large surface areas and abundant active sites were prepared via a wet chemical method. The HP PdRuCu NSs exhibit excellent HER activity with an ultra-low overpotential of 25 mV to achieve 10 mA cm −2 . The mass activity for GOR of HP PdRuCu NSs is 1083 mA mg −1 Pd, much higher than that of Pd black (347 mA mg −1 Pd ). The introduction of Ru and Cu atoms promotes the C–C bond cleavage and completely oxide glycerol without COads generation.